Risk factors influencing the building projects in Pakistan: from perspective of contractors, clients and consultants. Issue 6 (26th April 2022) - Kamal, Asad; Abas, Muhammad; Khan, Dildar; Azfar, Rai Waqas
Abstract: Risk management in construction projects is an important process to achieve the project objectives in terms of cost, quality and time. Construction projects faces delays, cost overrun and quality defects due to avoidance of risk factors by contractors, clients and consultants. So the present study aims to investigate the risk factors that influence project objectives namely cost, quality and time of building construction projects in Pakistan from perspective of contractors, clients, and consultants. Risk factors were selected from literature survey and were finalized after consultation with construction experts. A questionnaire survey was prepared and various construction professionals were approached for feedback. Based on feedback of 164 experts, collected data was analysed statistically and were ranked based on relative importance index. As per the survey results, inadequate project management is the most critical factor effecting time performance of construction projects, rework due to error effect cost performance, and poor supervision effect quality of construction projects. Additionally, the study will help in planning and monitoring stages of the projects and shall improve the performance of construction industry of Pakistan.